ULTRASONIC DISSECTION AND COAGULATION BY ATTACHMENT «HARMONIC FOCUS» IN ANATOMIC RESECTION OF THE LUNG - A. L. Akopov; A. . Karlson (Вестник хирургии имени И.И. Грекова)
The authors aimed to evaluate the efficacy of application of ultrasound dissection technology and coagulation by using «Harmonic Focus» (HF) instrument, while performing anatomical resection of the lung in open thoracic surgery. The method was carried out in serial 20 patients with lung cancer, whom the lung anatomical resection was performed. A long attachment (17 cm) with curved branches was applied. There were 11 lobectomies and 9 pneumoectomies. The application of HF allowed the dissection of pleural adhesions, pulmonary ligament, a separation of roots of the lung elements, lymphatic nodes of roots of the lung and mediastinum, in spite of being very close to vessels. A fatty tissue of the mediastinum was removed quickly and practically without blood. The HF considerably accelerated the process of vessel treatment, especially, while performing the lobectomy. At the same time, the attempts of application of HF instrument for separation of interlobal fissure resulted in not quite satisfactory aerostasis and hemostasis. The duration of the lobectomy was 127±35 minutes at the average and in the case of pneumoectomy, it consisted of 120±45 minutes. An intraoperative hemorrhage was 300±145 ml. A quantity of exudates was 440±280 ml by drainage on the first day. The pleural cavity drainage was used during 3±1 days. The HF instrument, which was applied for ultrasonic dissection and coagulation, was characterized by multifunctionality and simplicity of usage. It was recommended for a wide application in the thoracic surgery for performing the anatomical lung resections by thoracotomy method.